2020
DOI: 10.1177/1475921720965122
|View full text |Cite
|
Sign up to set email alerts
|

Time reversibility of Lamb waves in thin plates with surface-bonded piezoelectric transducers is temperature invariant at the best reconstruction frequency

Abstract: The Lamb wave time-reversal method has been widely proposed as a baseline-free method for damage detection in thin-walled structures. Under varying thermal environments, it would require that the time reversibility of Lamb waves is temperature invariant. In this study, we examine the temperature dependence of Lamb waves and its time reversibility using experiments and finite element simulations on isotropic plates with surface-bonded piezoelectric wafer transducers for actuation and sensing. The study is condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Various subsequent studies 43,44,50 have since established the efficacy of the RTRM using f rc and the extended wave packet in room temperature.…”
Section: Refined Time-reversal Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various subsequent studies 43,44,50 have since established the efficacy of the RTRM using f rc and the extended wave packet in room temperature.…”
Section: Refined Time-reversal Methodsmentioning
confidence: 99%
“…Lamb waves were generated in the plate by exciting one of the transducers with a five-cycle Hann window modulated sinusoidal tone burst signal of 20 V peak amplitude. 44 The central frequency of the input excitation was chosen with in a range such that it actuates only S 0 and A 0 modes. The voltage of the top electrode of the other transducer (sensor) was recorded after applying a 10 dB gain with a sampling frequency of 72 MS/s.…”
Section: Methodsmentioning
confidence: 99%
“…For further validation, the present solution is also compared with the experimental results presented by Sharma et al (2020) for a similar system as in Figure 3 with the same plate and adhesive layer thickness but with transducers of 0.25 mm thickness. The transducer size used in the experiment is 10 mm, but a reduced size of 9 mm is considered for the 2D FE simulation and the analytical solution to compensate for the possible weak bonding around the edges of the transducer in the experimental set-up (Sharma et al, 2020).…”
Section: Validationmentioning
confidence: 99%
“…For further validation, the present solution is also compared with the experimental results presented by Sharma et al (2020) for a similar system as in Figure 3 with the same plate and adhesive layer thickness but with transducers of 0.25 mm thickness. The transducer size used in the experiment is 10 mm, but a reduced size of 9 mm is considered for the 2D FE simulation and the analytical solution to compensate for the possible weak bonding around the edges of the transducer in the experimental set-up (Sharma et al, 2020). A recent study (Agrahari and Kapuria, 2016a) has shown that although a full-field 3D FE solution differs from the simplified plane strain 2D FE solution in terms of actual magnitude of the voltage response, the two solutions match well when they are normalized with respect to their respective peaks.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation